Clinical Potential of miR-451 and miR-506 as a Prognostic Biomarker in Patients with Breast Cancer. (11th January 2022) - Du, Yu; Miao, Zhuang; Qiu, Lijuan; Lv, Yan; Wang, Kedi; Guo, Lusheng
Abstract : Background . The incidence and mortality of breast cancer in the world remain high. The function and important role of miR-451 and miR-506 in a series of cancers have been proved. The purpose of this research was to explore the clinical diagnosis and prognostic significance of miR-451 and miR-506 expression in breast cancer. Methods . Quantitative real-time polymerase chain reaction (qRT-PCR) was applied to detect miR-451 and miR-506 expression in serum and tissues. The relationship of miR-451 and miR-506 with clinical parameters was determined by the chi-square test. Receiver operating characteristics (ROC) analysis was conducted to evaluate the diagnostic accuracy of miR-451 and miR-506 in breast cancer. In addition, we determined the prognostic performance of miR-451 and miR-506 using Kaplan–Meier survival assay. Results . The expression of miR-451 and miR-506 in breast cancer patients was significantly lower than that in healthy people. miR-451 and miR-506 expression decreased in breast cancer tissues compared with paracancerous tissue. High expression of miR-451 and miR-506 was associated with positive lymph node metastasis and late tumor node metastasis stage. Breast cancer patients with high miR-451 and miR-506 expression had lower five-year survival rate. The level of miR-451 and miR-506 expression showed high diagnostic accuracy for distinguishing breast cancer patients and healthy people. Conclusion . miR-451 and miR-506 could be used as biomarker for the diagnosis and prognosis of breast cancer.